Revolutionizing Healthcare: Embracing Robotics and AI for Enhanced Patient Care - Ausaf Butool; Asna Soha; Syeda Mariyam; Zainab Hussain; Anupama Koneru (International Journal of Pharmacy and Analytical Research, 2026)
This review enlightens the emerging role of artificial intelligence (AI) and robotics in the healthcare field. AI works with an amalgamation of extensive amounts of data using quick and complex algorithms. This allows the software to promptly adapt the pattern of the data characteristics. The use of AI along with robotics in the healthcare sector has shown an astounding rising trend in the past decade. The progressive advancements in big data analytics, cloud computing and artificial intelligence have led to increased research and development of intelligent robots in all walks of human life. Functions like conducting routine checkups, assisting surgery, streamlining hospital logistics are some of the tasks that may be carried out with great efficiency with the use of artificial intelligence in hospitals across the globe. Major advantages of application of robotic and AI in surgeries include better visualization, enhanced dexterity, greater precision, safer working conditions, operational tasks organized to perfection, etc. The future of this remunerative industry is anticipating a great revolution, aiming to create intelligent machines that work like humans. The perspective of AI and robotics in the future for healthcare sector comprises the care of geriatric population, discovery of new drugs, diagnosis of fatal diseases, elevating the clinical trials, predicting epidemic outbreaks, etc. However, the permanence of using robotics in health services may be questionable in terms of disbursement, conventional mindset of people. Robotics and AI in surgery is still in its infancy and its niche has not yet been chiseled. The present article accentuates AI’s ability to revolutionize surgeries and its role in shaping the future of healthcare. This article gives a vast overview of AI in medicine, dealing with the terms and concepts as well as the present and future applications of AI. It aims to enhance knowledge and acquaintanceship of AI among primary healthcare physicians.